Language and Instructional Methodology CLIL in Pharmacy Universities (Journal of Science-Innovative Research in Uzbekistan, 2023)
Content and Language Integrated Learning (CLIL) has certainly attracted a lot of attention among educators and practitioners in Europe and around the world during the last two decades. This results in a reasonably quick progress toward a theoretical and practice-oriented paradigm for CLIL implementation (Coyle, 2015). According to recent sources, this present instructional technique has been implemented into the school systems of more than 40 European countries at various educational levels. The status of English in Asian countries may play critical roles in the globalized world, such as teaching English to accelerate national growth, learning other cultures, and teaching English as a medium of international communication (Chang, 2011).